PRODUKTIVITAS TENAGA KERJA DAN PENDAPATAN USAHATANI TEGAL (STUDI KASUS DI DESA KEDUNGORI) - Sudalmi, Endang Sri (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACT The aim of this research is to know the labor’s productivity and the income that is aimed from the farming business. This research used Study Cases method with the direct observation over Mr. Sutejo’s farming business in Kedungori village, Kecamatan Dempet, Kabupaten Demak during 2008 who has 1 acre farming land. The results of this research are: 1. The highest labor’s productivity in the second planting period is in amount of Rp. 401.590, 91per male week days.2. The farming business highest income in the first planting period is in amount of Rp. 39.651.000 per acre. Key words: Farming business, labor’s productivity, farmer’s income.